THE EFFECTS OF EXERCISE THERAPY IN THE TREATMENT OF PRIMARY FIBROMYALGIA PATIENTS - Deniz Evcik,; Füsun Aytaç, (Archives of Rheumatology, 2001)
Primary fibromyalgia sendrome (FMS) is a very common rheumatological diagnosis and there are various treatment modalities. The aim of this study is to investigate the effects of therapy (home and group therapy) in the treatment of FMS. A total of 62 primary fibromyalgia patients according to American College of Rheumatology (ACR) criteria were included the study. Their ages ranged between 32-60. Patients were randomly assigned in to three groups. None of them had a practice of daily simple exercise program or group aerobic therapy at least three years. Group 1 (n=21) were given home exercise program. Group 2 (n=21) joined the aerobic sessions with group therapy three times per week. Group 3 (n=20) were accepted as control group. Patients were evaluated by the number of tender points, Visuel Analog Scale (VAS) for pain and Fibromyalgia Impact Questionnaire (FIQ). After treatment, in group 2 there was statistically significant difference in the number of tender points, VAS and FIQ (p<0,001) Also in group 1 there was an improvement in VAS and FIQ but not in the number of tender points compared to the control group (p<0,01). Patients with FMS mostly complain about the pain and the difficulty in daily living activities. This study shows that exercise therapy either at home or in group sessions is effective in treating fibromyalgia patients. It is also a good motivating factor for patients who mostly spend their time at home, in a sedantery life style.